Conservative superficial parotidectomy - Puig, Roberto; Sarroca, Carlos (Cirugía del Uruguay, 1975)
Conservative superficial parotidectomy is, at present, tbe surgery of choice in most parotid tumors. The pn,sent work discusses the surgical anatomy of i.he area, and the arrangement in dil'ferent layers of the vascular ,md nervous elements of the gland. The different stages of the procedure are. described in their due order.